2019
DOI: 10.3390/molecules24173203
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial Activity of Essential Oils from the Aerial Parts of Pinus eldarica Grown in Northwestern Iran

Abstract: Pinus eldarica (Pinaceae), an evergreen plant, is distributed across the warm and dry climates of western Asia, including Asia Minor, the Middle East, and land surrounding the Caspian Sea. Essential oils (EOs) from different aerial parts of this tree have been used in traditional medicine. We aimed to investigate the chemical profile and antimicrobial activity of the EO from P. eldarica grown in northwestern Iran. EO from the needles, bark, and pollen were extracted with boiling water using a Clevenger apparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Furthermore, the antimicrobial activity presented by the WW and HApWW samples is strongly correlated with the presence of the major constituents α-Fenchene, Sabinene, β-Thujene, β-myrcene and methyl salicylate, which were reported to possess good antimicrobial activity against microbial strains such as E. coli, B. subtillis, P. aeruginosa, S. cerevisiae and C. albicans [57]. Moreover, the studies reported by Ghaffari et al [58] regarding EOs having most abundant chemical constituents β-pinene, β-myrcene, limonene, and caryophyllene also demonstrated antimicrobial activity against some highly susceptible strains such as E. coli, C. albicans, and S. aureus. Furthermore, the antimicrobial activity of the investigated samples could also be attributed to the less abundant constituents of the WW EO such as 1,8-Cineole, γ-Terpinene and β-Pinene which were previously reported as having antimicrobial activity against a wide range of microbial strains [59,60].…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, the antimicrobial activity presented by the WW and HApWW samples is strongly correlated with the presence of the major constituents α-Fenchene, Sabinene, β-Thujene, β-myrcene and methyl salicylate, which were reported to possess good antimicrobial activity against microbial strains such as E. coli, B. subtillis, P. aeruginosa, S. cerevisiae and C. albicans [57]. Moreover, the studies reported by Ghaffari et al [58] regarding EOs having most abundant chemical constituents β-pinene, β-myrcene, limonene, and caryophyllene also demonstrated antimicrobial activity against some highly susceptible strains such as E. coli, C. albicans, and S. aureus. Furthermore, the antimicrobial activity of the investigated samples could also be attributed to the less abundant constituents of the WW EO such as 1,8-Cineole, γ-Terpinene and β-Pinene which were previously reported as having antimicrobial activity against a wide range of microbial strains [59,60].…”
Section: Resultsmentioning
confidence: 91%
“…The first compound, detected at RT 11.945 min, showed SI of 88 with Methanoazulen-9-ol, decahydro-2, 2, 4, 8-tetramethyl-stereoisomer, which belonged to the class sesquiterpene and possessed antibacterial as well as antioxidant properties [73]. This compound was earlier reported as a major component of plant essential oils [74,75] but there are no reports on this from microbial sources as yet. Another compound in ADR1 metabolite extract was detected at RT 14.519 min, which showed SI of 90 with 5-z-methyl-2-z-hydroxycarbonyl-5-e-ethenyl-4-z-propen-2-ylcyclohexanone, was a terpenoid having structure similar to Asperaculane B, a known GABA-transaminase inhibitor having significance in epilepsy treatment [76].…”
Section: Secondary Metabolite Profiling and Gc-ms Analysis Of Metabolmentioning
confidence: 95%
“…J. 25 (1): [21][22][23][24][25][26][27][28][29][30][31][32] Meanwhile, it would be interesting to identify the key compounds contributing to these activities to accurately evaluate the influence of different solvents on the extraction of phenolic constituents and the association between their compositions and the resulting activities. Taken together, A. repens extracts have been found to be a promising antioxidant-rich therapeutic component with antimicrobial and enzyme inhibitory features for the food and pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 99%
“…J. 25 (1): [21][22][23][24][25][26][27][28][29][30][31][32] Synthetic antioxidants such as, tertiary butyl hydroquinone, BHA, and butylated hydroxyltoluene are widely used in food industry [5] . Long-term consumption of synthetic antioxidants, however, is always accompanied with various risks for health [6] .…”
Section: Introductionmentioning
confidence: 99%